Analgesic Effect of Ethanol Extract of Dillenia ochreata (Miq.) Teijsm. & Binn. Ex Martelli in Wistar Rats - Yohandini, Heni; Ghaniya, Fahdelaa; Muharni, Muharni; Fitrya, Fitrya (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
Dillenia ochreata is a traditional medicine used to treat wounds and scabies. In wound healing, one of the treatments is to reduce pain (analgesic). Some compounds of triterpenoid groups have been known to be active as analgesic compounds. The leaf of D. ochrea was reported to contain secondary metabolites triterpenoid centulic acid and 3β-glucopyranosyl-lup-20(29)-en-28 oat. This study aimed to evaluate the analgesic activity and standardization of the ethanol extract of D. ochreata leaf and determine the mechanism of action. Analgesic activity was determined by a hot plate method and formalin test, and the mechanism of action was through muscarinic, dopamine, and opiate receptors, standardization of extract using the method issued by the Indonesian Ministry of Health. The ethanol extract of D. ochreata leaf at a 400 mg/kg bw dose has higher analgesic activity (24.85%) than the positive control (18.32%). Statistical analysis showed a significant difference in analgesic activity percentage between the positive group and those with a 400 mg/kg bw group dose. The 400 mg/kg bw dose also showed a significant difference (p<0.05) between neurogenic pain (46.92%) and inflammation (61.19%) in the formalin test caused by opioid receptors. The evaluation of the analgesic mechanism showed the ethanol extract of D. ochreata leaf works through opioid receptors. The extract meets the requirements of the standard parameters. The leaf extract of D. ochreata can be developed as an anti-analgesic from natural medicine.